Trends in the study of leadership with a focus on the standard model of Fromm and Wheaton: A field study of a sample of administrative leaders in the Iraqi government sector. - Muhammad Hussein Al Yassin (Iraqi Journal for Administrative Sciences, 2024)
The bulk of administrative studies during the last thirty years have been focused on one topic, which is the effectiveness of leadership. Given that leadership activity in organizations is affected by three basic variables: the leader, the situation, and the subordinates, and given that these variables are predominantly human, behavioural psychologists, sociologists, and science have found That social psychology is an opportunity to conduct many studies and promote many theories in the field of leadership, and although we do not deny the importance of these efforts, nor the value of the dimensions added to the subject of leadership as a result of this research, the applied value of most of the models that emerged from these studies was. According to the administrative point of view, there are limited benefits. To demonstrate the previous opinion, suffice it to say that in addition to the studies that focused on the personal characteristics that characterize the leader, other studies assume that the leader's effectiveness is determined by variables related to his behaviour. Other studies also focused on situational variables, while another group focused on the interaction of the leader's characteristics. Position characteristics. Recently, another group of studies focused on the concepts and principles of learning and reinforcement. These studies focused on the supportive characteristics of leader behaviour. These practical studies view leadership as a process of support and that leaders are a source of support, as the leader provides reward and punishment conditional on performance as a means of influencing the level of performance. Subordinates Last - but not least - the integrative theory suggests that the starting point for analyzing and interpreting the effectiveness of leadership influence is the behaviour of subordinates, and therefore, building a comprehensive or integrated theory of the effectiveness of leadership influence requires analyzing the various factors that affect the individual's behaviour. As a result of the multiplicity of studies and research in a previous manner, it was natural for leadership models and styles to multiply, and the multiplicity was not limited to leadership styles only but extended to include variables influencing both the leader's behaviour and the behaviour of subordinates (Sharif and Al-Deeb (1985). This research deals with a brief review of the most important of these models and patterns, leading to the standard model of leadership presented by (Vroom & Yetton, 1973), and an attempt to use the scale of this model in application to the Iraqi reality to explore the prevailing leadership styles among administrative leaders in state agencies and departments in Iraq.